2009
DOI: 10.1111/j.1574-0862.2009.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural nonfarm income and its impact on agriculture: evidence from Albania

Abstract: Using data from the 2005 Albania Living Standards Measurement Study (ALSMS05) survey, this article analyzes the overall impact of household nonfarm income-generating activities (RIGA) on agricultural expenditures as well as technical efficiency of rural farm households. We also differentiate the impact for subsistence and commercial farmers, who are in the top 25% of the distribution of value of annual agricultural sales. Our results show that on the whole, Albanian rural households utilize their nonfarm earni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 24 publications
9
65
2
3
Order By: Relevance
“…The outcome also depends on development opportunities and household strategies in a specific context. For instance, Kilic et al (2009) found that rural households in Albania tend to use their off-farm earnings to move out of agriculture, whereas Oseni and Winters (2009) showed that offfarm activities in Nigeria help households to improve their farm production through higher input use, including more employment of hired labor. This is consistent with our sample data where households with off-farm income use more fertilizer, pesticides, and hired labor and obtain an almost 10% higher food output per AE than households without off-farm income.…”
Section: Explaining Structural Relationsmentioning
confidence: 99%
“…The outcome also depends on development opportunities and household strategies in a specific context. For instance, Kilic et al (2009) found that rural households in Albania tend to use their off-farm earnings to move out of agriculture, whereas Oseni and Winters (2009) showed that offfarm activities in Nigeria help households to improve their farm production through higher input use, including more employment of hired labor. This is consistent with our sample data where households with off-farm income use more fertilizer, pesticides, and hired labor and obtain an almost 10% higher food output per AE than households without off-farm income.…”
Section: Explaining Structural Relationsmentioning
confidence: 99%
“…Under the null hypothesis that the error terms are uncorrelated with all the regressors against the alternative that they are correlated with at least some of the regressors, an F-test is performed [42]. The instrumental variables approach has been used in several recent studies of agricultural production analysis [43][44][45][46][47].…”
Section: Analytical Framework and Empirical Modelmentioning
confidence: 99%
“…For example, Mochebelele and Winter-Nelson (2000), Tijani (2006), Haji (2007), Pfeiffer et al (2009), Bojnec and Ferto (2013), and Babatunde (2013) found a positive significant impact of off-farm income on farm efficiency. There are also cases (such as Goodwin and Mishra (2004), Chang and Wen (2011), and Kilic et al (2009)) in which participation in off-farm activities has an adverse effect on the agriculture. They argued that if the income from the off-farm activities is more attractive than the agriculture, farmers might give less attention for the agriculture and they might devote more family labor and time for off-farm activities.…”
mentioning
confidence: 99%
“…Off-farm income can also enhance agricultural production by relaxing liquidity and credit constraints to purchase productivity enhancing agricultural technologies such as improved seed, fertilizer, machineries, and hiring labor (Ruben 2001;Lamb 2003;Matshe and Young 2004;Kilic et al 2009;Oseni and Winter 2009;Anriquez and Daidone 2010). This is particularly true in developing countries where farmers are facing credit constraints (Stampini and Davis 2009).…”
mentioning
confidence: 99%